Distribución de los esfuerzos en tramos protésicos fijos de tres unidades con elementos intrarradiculares colados y prefabricados: análisis biomecánico utilizando un modelo de elementos finitos (2009)
ABSTRACT: his study analyzes the behavior of stress distribution in three-unit fixed partial dentures (FPD) using a finite elements model (FEM). Methods: a canine and a central incisor were modeled; both of them were joined together by a FPD with a lateral incisor as pontic. Endodontic treatment with a 4 mm apical seal was simulated for abutment teeth; cast post and cores and prefabricated posts were modeled for abutments and a noble metal framework veneered with porcelain was used as the final restoration. For better precision, a three-dimensional model of supporting structures such as cortical bone, trabecular bone and periodontal ligament was designed. Software capable of showing the behavior of bodies when different mechanical properties are introduced to the system was used. Oblique loads of 1N in a 45° angle were applied on the cingulum area of both abutments and pontic which was intended to show the distribution of stress without failing. Results: the greatest strain was found on both the canine and central incisor dentine where fiber posts were used (0.92 N/mm2 cast post and core, 1.17 N/mm2 fiber post on the canine; 1.11 N/mm2 cast post and core, 1.92 N/mm2 fiber post for the central incisor). Conclusions: distribution of von Misses stress was found to be similar to that of single tooth. When rigid intraradicular elements were used, this element absorbs most of the energy. The decision of which element is better depends on different variables.